Enhancing Students’ Knowledge of First Aid through Online Training - Richard De Ocampo; Benjamin Manuel; Ron Matthew Ramos; Darin Jan Tindowen (Formosa Publisher, 2023)
This study aimed to evaluate the effectiveness of an online first aid training program in enhancing the knowledge of Bachelor of Physical Education (BPEd) students. This quasi-experimental study involved 23 BPEd students enrolled in the first semester of the Academic Year 2020-2021 at the University of Saint Louis Tuguegarao. Results showed a significant improvement in post-test scores compared to pre-test scores, indicating that the training effectively enhanced the participants' knowledge of first aid. Furthermore, the participants' overall evaluation of the online training was highly satisfactory. In conclusion, the findings demonstrate that Project L.I.F.T. (Learning Innovative First Aid Training) was successful in increasing the first aid knowledge of BPEd students, proving the effectiveness of online training as an alternative to traditional face-to-face instruction.